Using 3D printing for complex pediatric transplantation: an interview with Pankaj Chandak. Issue 1 (January 2017) - Chandak, Pankaj
Pankaj Chandak speaks to Alexandra Thompson, Senior Editor Pankaj Chandak is a Specialist Registrar in Transplant Surgery at Guy's, St Thomas' and Great Ormond Street Hospitals and a Royal College of Surgeons of England Research Fellow at King's College London under Professor Nizam Mamode, Professor Anthony Dorling and Mr Chris Callaghan. Having qualified from Guy's, King's and St Thomas' University of London, Pankaj was Anatomy Demonstrator under Professor Harold Ellis and is currently a member of the Teaching Faculty of Surgical Anatomy at the Royal College of Surgeons. He has been awarded The Royal College of Surgeons of England Arnott Lecture and Medal for 2016 and The Royal College of Surgeons of England Lister Essay Prize and Medal. His interests include pediatric transplantation, organ perfusion, innovation and public engagement in science. His multidisciplinary work on integrating 3D printing into complex pediatric transplantation as a world first was awarded The Royal Society of Medicine Norman Tanner Medal and the prestigious Worshipful Company of Cutlers' Clarke Medal and Prize, 2016. He has been invited lecturer at The British Science Festival, The Royal Institution in London and The Royal College of Surgeons Hunterian Museum amongst others. The original 3D model created by the team has been accepted by The Science Museum (London, UK) for permanent exhibition in the Medical Gallery. Mr Chandak was elected a Fellow of the Royal Asiatic Society.